Answer:
2
Explanation:
Simplifying
9c + -7 = 7c + -11
Reorder the terms:
-7 + 9c = 7c + -11
Reorder the terms:
-7 + 9c = -11 + 7c
Solving
-7 + 9c = -11 + 7c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-7c' to each side of the equation.
-7 + 9c + -7c = -11 + 7c + -7c
Combine like terms: 9c + -7c = 2c
-7 + 2c = -11 + 7c + -7c
Combine like terms: 7c + -7c = 0
-7 + 2c = -11 + 0
-7 + 2c = -11
Add '7' to each side of the equation.
-7 + 7 + 2c = -11 + 7
Combine like terms: -7 + 7 = 0
0 + 2c = -11 + 7
2c = -11 + 7
Combine like terms: -11 + 7 = -4
2c = -4
Divide each side by '2'.
c = -2
Simplifying
c = -2